The Influence of Hydrogen on the Process of Plastic Flow Self-Organization in Ti - Lunev A. G. Alexey Gennadievich; Nadezhkin M. V. Mikhail Vladimirovich; Barannikova S. A.; Zuev L. B.; Ionova N. A. (Advanced Materials and Alloys, Nanomaterials and Nanotechnology, 2016)
Title screen